Factors Related To The Incidence Of Preterm Delivery In The Room Maternity Hospitals dr. H. Moch. Ansari Saleh Banjarmasin - Ahmad Hidayat; Dewi Pusparani Sinembela; Dewi Agreni (Universitas Sari Mulia, 2018)
Background: The prematurity is one of cause of death the baby in Indonesia. It is estimated that the preterm labor contribution to the infant mortality rate reached 60-80%. Incidence the preterm labor for the past two years at RSUD Dr. H. Moch. Ansari Saleh Banjarmasin continues to rise, 2014 is 129 cases and 2015 increased to 223.Purpose: Analyze factors that deals with genesis preterm labor.Methods: Using survey analytic with the approach case control. Population all maternity mother. The sample of the cases 233 with a total of sampling, sample control 466 with systematics random sampling. Analysis data is bivariat by test Chi Square (Î±=0.005) and Odds Ratio.Results: Analysis bivariat test chi square show there was a correlation age mother (Ï=0,001) (or= 1,199), paritas (Ï= 0,000) (OR= 1,880), the distance pregnancy (Ï=0,001) (OR=1,179), gamelli (Ï=0,000) (OR=0,034) with genesis preterm labor.Conclusion: There was a correlation age mother, paritas, the distance pregnancy, gamelli in the genesis preterm labor. Age mother risk (20 andÂ 35) years had a chance 1,199 times greater to bore in the gestastional age preterm, mother with of paritas risk (1 and 3) had a chance 1,880 times greater to bore in the gestastional age preterm , mother with the distance pregnancy risk (2 years) had a chance 1,179 time greater to bore in the gestastional agre preterm and mother with gamelli had a chance 0,034 time greater to bore in the gestastional age preterm.Keywords: Preterm Labor, Mother Age, Paritas, The Distance Pregnancy, Gamelli.Â